Development of Learning Management of E-learning in Demak Senior High School 1 - Chaliyyah, Nafisatul; Ekosiswoyo, Rasdi; Sudana, I Made (Educational Management, 2019)
This study aims to develop an e-learning management model of learning for Mathematics subjects in class X Senior High School 1 in Demak, testing its effectiveness and practicality. The research method used is Research and Development with the stages of this research process include: (1) preliminary stage; (2) the development stage, making the learning management model integrated into e-learning; (3) the validation stage, carried out by experts and practitioners; and (4) the testing phase was carried out in Demak 1 State High School involving 12 limited test students and 36 wider test students. Methods of data collection were in the form of test questions and questionnaires. The product validation test results were 94.35% (very feasible). Limited test results obtained an average score of pre-test 74.67 and post-test of 80.08 with a gain of 0.33 (medium). Wider test results obtained an average score of pre-test 71.44 and post-test 84.67 with a gain of 0.41 (medium). The practicality test results were obtained from student responses, namely 91.17% which included in the very practical category.